1992
DOI: 10.1128/jb.174.17.5669-5675.1992
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of aromatic dehalogenases of Mycobacterium fortuitum CG-2

Abstract: Two different dehalogenation enzymes were found in cell extracts ofMycobacteriumfortuitum CG-2. The first enzyme was a halophenol para-hydroxylase, a membrane-associated monooxygenase that required molecular oxygen and catalyzed the para-hydroxylation and dehalogenation of chlorinated, fluorinated, and brominated phenols to the corresponding halogenated hydroquinones. The membrane preparation with this activity was inhibited by cytochrome P-450 inhibitors and also showed an increase in the A4,, caused by CO. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 27 publications
0
35
0
Order By: Relevance
“…Recently, several kinds of bacterial monooxygenases involved in the hydroxylation of halophenols have been characterized. Two cytochrome P-450 membranebound enzymes have been identified from Rhodococcus chlorophenolicus (19) and Mycobacterium fortuitum (18). Two soluble flavin-containing monooxygenases have also been isolated and purified: (i) a 2,4-dichlorophenol hydroxylase which catalyzes the ortho hydroxylation of 2,4-DCP (14) and (ii) a pentachlorophenol hydroxylase from a Flavobacterium sp.…”
Section: Vol 177 1995mentioning
confidence: 99%
“…Recently, several kinds of bacterial monooxygenases involved in the hydroxylation of halophenols have been characterized. Two cytochrome P-450 membranebound enzymes have been identified from Rhodococcus chlorophenolicus (19) and Mycobacterium fortuitum (18). Two soluble flavin-containing monooxygenases have also been isolated and purified: (i) a 2,4-dichlorophenol hydroxylase which catalyzes the ortho hydroxylation of 2,4-DCP (14) and (ii) a pentachlorophenol hydroxylase from a Flavobacterium sp.…”
Section: Vol 177 1995mentioning
confidence: 99%
“…Previous studies involving non-CF patients have reported other NTM species, such as Mycobacterium kansasii, to be associated with residence in nonrural areas (20). Moreover, several studies have suggested that certain chemical compounds present in polluted water distribution systems stimulate the growth of NTM (28). Air pollution in cities may also contribute to NTM lung disease by interfering with the mucosal immune system.…”
mentioning
confidence: 99%
“…The strains which we studied are able to degrade several chlorinated phenols, guaiacols, and syringols (2,19,20,24), and they also 0-methylate various chlorinated phenolic compounds (24); however, there are some differences in substrate specificity. The M. chlorophenolicum strains, as well as a strain of M. fortuitum (35), degrade pentachlorophenol via two hydroxylations, followed by reductive dechlorinations, producing 1,2,4-trihydroxybenzene, which is mineralized to CO, (3,4,20,22,24,45,46). Interestingly, these polychlorophenol-degrading strains did not utilize most of the nonhalogenated aromatic compounds which we tested ( Table 4).…”
Section: Resultsmentioning
confidence: 99%